Promoter engineering with programmable upstream activating sequences in Aspergillus Niger cell factory - Xiaomei Zheng; Yuting Guo; Meiling Chen; Yudan Lu; Yimou Du; Yu Lei; Ping Zheng; Jibin Sun (Microbial Cell Factories)
Abstract Background Aspergillus niger is an important industrial filamentous fungus used to produce organic acids and enzymes. A wide dynamic range of promoters, particularly strong promoters, are required for fine-tuning the regulation of gene expression to balance metabolic flux and achieve the high yields of desired products. However, the limited understanding of promoter architectures and activities restricts the efficient transcription regulation of targets in strain engineering in A. niger. Results In this study, we identified two functional upstream activation sequences (UAS) located upstream of the core promoters of highly expressed genes in A. niger. We constructed and characterized a synthetic promoter library by fusing the efficient UAS elements upstream of the strong constitute PgpdA promoter in A. niger. It demonstrated that the strength of synthetic promoters was fine-tuned with a wide range by tandem assembly of the UAS elements. Notably, the most potent promoter exhibited 5.4-fold higher activity than the strongest PgpdA promoter reported previously, significantly extending the range of strong promoters. Using citric acid production as a case study, we employed the synthetic promoter library to enhance citric acid efflux by regulating the cexA expression in A. niger. It showed a 1.6-2.3-fold increase in citric acid production compared to the parent strain, achieving a maximum titer of 145.3 g/L. Conclusions This study proved that the synthetic promoter library was a powerful toolkit for precise tuning of transcription in A. niger. It also underscores the potential of promoter engineering for gene regulation in strain improvement of fungal cell factories.